PENGELOLAAN KELEMBAGAAN RESIMEN MAHASISWA BATALYON 041/ INDRA BUANA UNIVERSITAS RIAU - Yuli Rahmawati; Daeng Ayub Natuna; Jaspar Jas (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abtrack: The aim of this study was to describe the institutional management of the Student Regiment Batalyob 041 / Indra Buana University of Riau with regard to planning, organization, leadership and supervision. This study uses a descriptive method with a qualitative approach aimed at knowing the institutional management of the student regiment. This study consists of one variable, namely Management of Student Regiment 041 / Indra Buana University Riau Battalion with 4 indicators. The test subjects were 4 people consisting of 2 key informants, 1 control person and 1 observer-informant. Techniques used for data collection are documentation, observation and interviews. Data analysis techniques make use of data reduction, display data and conclusion drawing. The results of this study indicate that the management of the Battalion 041 / Indra Buana University Student Regiment with 4 indicators in management that are not suitable there are 2 indicators, namely 1) organizing indicators, 2) leadership indicators. In the organizing indicator where the recruitment of new members has decreased compared to the previous year, in which organization is an important factor in an organization. During the leadership indicators there are still members who do not perform the tasks and responsibilities that have been entrusted. To overcome this mismatch, the manager is expected to increase the organization in recruiting new members and to pay more attention to members in the form of giving motivation to be more responsible in performing their duties and responsibilities to get many successors in the Student Regulations 041 / Indra Buana University of Riau Battalion. Then for the University of Riau to assist in the process of organizing so that the institutions around the campus will live with the many students who take extracurricular activities.Key Words: Management, Institution, Student Regiment